Strategy Implementation Styles Of Malaysian, Thai And Hungarian Middle Managers - P. Joshi, Maheshkumar; D. Sherman, Hugh; Schermerhorn, John R. (Asian Academy of Management (AAM), 2004)
There is a need for more comparative empirical research that examines middle manager roles in strategic change. This paper reports a study of middle managers in two dynamic settings: the Asia/Pacific region – Malaysia and Thailand; and Central/Eastern Europe – Hungary. Results of 213 respondents across three countries indicate that middle managers from all three tend toward use of authoritarian management styles even in proactive strategic change situations. However, Hungarians are less likely to use these styles than Thai and Malaysian middle managers. For all three countries, managers with less work experience were found to have lower tendencies to use an authoritarian style of implementation. When top managers exhibit an aggressive strategic posture, middlemanagers from all three countries are also less likely to use an authoritarian style.